Coal hydrogasification: Entrained flow bed design-operation and experimental study of hydrogasification characteristics. (15th February 2018) - Yuan, Shenfu; Bi, Jicheng; Qu, Xuan; Lu, Qiuxiang; Cao, Qiue; Li, Wei; Yao, Guini; Wang, Qiufeng; Wang, Jiliang
Abstract: Coal hydrogasification processes including wire-mesh grid reactor, batch reactor, curie-point pyrolyzer, fixed bed reactor and so on were utilized or developed in laboratory researches. Although the experimental results could help to understand the basic behavior of coal hydrogasification, it was difficult to directly utilize such data for devising a new hydrogasifier. This paper designed a continuous entrained flow bed facility and described the hydrogasification characteristics. This device (15–30 kg/d) mainly consisted of a high-H2 pressure feed system, a high-temperature tube reactor. The capabilities were shown as follows: the temperature from 700 °C to 850 °C, H2 pressure from 0.1 MPa to 3.0 MPa, isothermal zone 300–600 mm, feeding rate from 15 to 30 kg/d and water yield was easy to obtained by tar-water separation. The good mass balance on the carbon and weight basis was established by analyzing the product distribution in detail. The results showed the yields of CH4 and light aromatic hydrocarbons increased through hydrogenation of tar and volatiles, hydrogasification of coal char. Although the small pilot plant had high heat loss through refractory with increasing H2 pressure, the typical results obtained from the continuous stable operation of the entrained flow bed reactor confirmed the design of new large-scale hydrogasification process was technical feasibility. Highlights: The continuous device operated under high temperature and H2 pressure. The water could easily collect and remove through tar-water separation. The highest sums of CH4, benzene and naphthalene yields were obtained. The pilot test confirmed the technical feasibility of design of new hydrogasifier.